-5y+19=-4y

Simple and best practice solution for -5y+19=-4y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5y+19=-4y equation:



-5y+19=-4y
We move all terms to the left:
-5y+19-(-4y)=0
We get rid of parentheses
-5y+4y+19=0
We add all the numbers together, and all the variables
-1y+19=0
We move all terms containing y to the left, all other terms to the right
-y=-19
y=-19/-1
y=+19

See similar equations:

| -6z-8=3z+19 | | 20t+15=19t | | (0)=−2x+3 | | 11c-48=8c | | 5-3x=-9x+17 | | C=2+3.14(•r) | | 8x+12=12x+4.8 | | -7+13n=12n+11 | | 6(1/2x+1/3)=3(x+4) | | 3t+43=6t-17 | | 38-6v=-(5v+8) | | 6x-9=3x-5+7 | | -8-4p=-16 | | -78=4x*26 | | n3=-20 | | -(9n-5)=-10+10(n-8) | | -2(1-x)+x=2x-7 | | -4t=20-8t | | 2x-(x-2)=x+32=3 | | 4-3d=+8 | | 3w-9=33.21 | | -(9n-5)=-10+10(n-80 | | -(-1+n)=-5 | | 6b-46=b+50 | | 3x+35=9x-7 | | 2=2x(-6) | | -3k+4=-2-2k | | -7x+5=4x-28 | | 7(2x-3)-9=3(2x+4)+2x | | -108=-9j | | 10x-13=6x+7 | | -9.4d-15.98=6.3+2.22-14.7d |

Equations solver categories